A Darwinian Pilgrim's Early Progress. (10th December 2018) - Ruse, Michael
Abstract : Part one of three in an autobiographical series which retraces the most significant events, collaborations, and research results of Michael Ruse's 55-year-long career in the history and philosophy of science. In this article, Ruse's Quaker roots, his subsequent loss of faith, and the first engagement with the study of natural science are recalled before delving deeper into his academic career. The main topics summarized in this walkthrough are considered chronologically as they developed: the epistemological demonstration that the Darwinian theory was not a narrative, or inferior, kind of science but a full-fledged, consilient research programme founded on genetics (early 1970s); the history of teleology in biological thought (mid-1970s); the sociobiology controversy (late 1970s); the so-called debunking argument and the is-ought fallacy (early 1980s).